2009
DOI: 10.1002/jps.21444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic-Activated Micellar Drug Delivery for Cancer Treatment

Abstract: The use of nanoparticles and ultrasound in medicine continues to evolve. Great strides have been made in the areas of producing micelles, nanoemulsions and solid nanoparticles that can be used in drug delivery. An effective nanocarrier allows for the delivery of a high concentration of potent medications to targeted tissue while minimizing the side effect of the agent to the rest of the body. Polymeric micelles have been shown to encapsulate therapeutic agents and maintain their structural integrity at lower c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 132 publications
(159 reference statements)
1
74
0
Order By: Relevance
“…The results from this study indicated that the permeability coefficient of glycerol not only in normal breast tissues, but also in breast cancer tissues after treatment with ultrasound is larger than that in tissues without ultrasound, moreover, there was a significant difference in relative permeability coefficient of glycerol between breast cancer tissues and normal breast tissues (p< 0.05). This phenomenon is consistent with the previous findings that ultrasound caused the increase of cell membrane permeability in TDD [77][78][79][80].…”
Section: Resultssupporting
confidence: 94%
“…The results from this study indicated that the permeability coefficient of glycerol not only in normal breast tissues, but also in breast cancer tissues after treatment with ultrasound is larger than that in tissues without ultrasound, moreover, there was a significant difference in relative permeability coefficient of glycerol between breast cancer tissues and normal breast tissues (p< 0.05). This phenomenon is consistent with the previous findings that ultrasound caused the increase of cell membrane permeability in TDD [77][78][79][80].…”
Section: Resultssupporting
confidence: 94%
“…This phenomenon is consistent with previous findings that ultrasound caused the increase of cell membrane permeability in TDD. [47][48][49][50] The quantitative reductions of attenuation coefficients at 60 min according to Eq. ͑3͒ for skin samples under different treatment procedures ͑40% G, 60% G, 80% G, 40% G/SP, 60% G/SP, and 80% G/SP͒ are shown in Figs.…”
Section: With Ultrasoundmentioning
confidence: 99%
“…The delivery of doxorubicin to cancer cells and tumors using drug loaded polymeric micelles combined with ultrasound has been pioneered by Rapaport, Pitt and coworkers and several excellent reviews are available [17,22]. The micelles used in these studies have focused almost entirely on the triblock copolymers of poly(ethylene oxide) and poly(propylene oxide) known as poloxamer or Pluronic ™ polymers [7,10,17,19,23].…”
Section: Introductionmentioning
confidence: 98%